Modelling of the Kinetics of Sulfure Compounds in Desulfurisation Processes Based on Industry Data of Plant; MATEC Web of Conferences; Vol. 85 : Chemistry and Chemical Technology in XXI Century (CCT 2016) - Krivtsova N. I. Nadezhda Igorevna (2016, 2016)
Title screen